Identification and functional validation of a new gene conferring resistance to Soybean Mosaic Virus strains SC4 and SC20 in soybean - Raza, Muhammad Muzzafar; Jia, Huiying; Razzaq, Muhammad Khuram; Li, Bowen; Li, Kai; Gai, Junyi (Frontiers in Plant Science, 2025)
Soybean Mosaic Virus (SMV) poses a serious threat to soybean production, often resulting in considerable yield losses or complete crop failure, particularly if infection occurs during early growth stages. While several SMV resistance genes have been identified, the genetic basis of resistance to certain strains remains poorly understood. Among the 22 SMV strains, SC4 and SC20 are considered pathogenic in Central China. Dominant genes resistant to SC4 (Rsc4) on Chr.14 in Dabaima and to SC20 (Rsc20) on Chr.13 in Qihuang-1 have been identified. Kefeng-1 is resistant to SC4 and SC20. This study aimed to determine whether the resistance to SC4 and SC20 in Kefeng-1 was identical and whether Rsc4 and Rsc20 in Dabaima and Qihuang-1 are also present in Kefeng-1 due to translocation. Mendelian experiments using F1, F2, and recombinant inbred lines (RIL3:8) of Kefeng-1 (resistant) and NN1138-2 (susceptible) indicated a single dominant gene inheritance pattern in SC4 and SC20, respectively. Linkage mapping showed two loci for SC4 and SC20 in neighboring single nucleotide polymorphism linkage disequilibrium blocks (SNPLDB) marker regions of 253 kb and 375 kb, respectively, in Kefeng-1. Association between SNPs in possible gene regions of Kefeng-1 and resistance data showed SNP11692903 jointly as the most significant SNP, exhibiting the highest χ2 value. By comparing SNP11692903 to possible gene sequences in the coding region, Glyma02g13380 was identified as a joint candidate gene. The results were validated using qRT-PCR, virus induced gene silencing (VIGS), and gene-sequence. Therefore, the two Mendelian genes on chromosome 2 in Kefeng-1 responsible for SC4 and SC20 resistance are unique genes, different from Rsc4 in Dabaima and Rsc20 in Qihuang-1. Hence, one gene is involved in resistance toward two SMV strains resistance. This result challenged our previous hypothesis of a single dominant gene responsible for resistance against a single strain and underscored the potential for using multiple resistance sources aimed at enhancing SMV resistance in breeding practices.